AN ANALYSIS OF THE STATE MEASURES TO SUPPORT THE PROGRAM FOR BUILDING SMALL HYDROPOWER PLANTS IN THE SOUTH RUSSIA - M. M. Gadyjev; S. A. Buchaeva (Финансы: теория и практика, 2017)
Currently in Russia the state support for building small hydropower plants is rather restricted. According to experts the legal standards for the development of Russian small hydropower plants should set to solve the problem. The article displays the results of an analysis of state measures to support programs for building small hydropower plants, including draft state program “Energy Efficiency and Energy Development” and the program “Fundamental objectives of state policy aimed to improve energy efficiency through the use of renewable energy sources for the period until 2020”. The authors systematize government documents on the development of small hydropower plants as well as strategic plans on financing and construction. Electric power industry policy in the area of development is not determined only by market indicators of commercial success. As in case of other basic industries, the results of its development have an impact on all aspects of country’s life. The article could be of interest to top and medium level managers involved in designing programs for the development of small hydropower plants.